Determinanty satysfakcji pracowników w modelu doskonałości EFQM - Jarzębiński, Marek (Determinants of Employees' Satisfaction in the Excellence Model EFQM, 2008)
The paper is an attempt to indicate main function areas of a quality system in an organization, which determine employee satisfaction. It reveals relevances of causal connections between elements of such management system and employee satisfaction. The subject matter of the study consisted of chosen categories (modules) of the EFQM Excellence Model. Basing on them, the causal model of employee satisfaction has been constructed. Using statistical methods, the author has verified detailed research hypotheses made in the study. They corroborate the causal relation between elements of management system and employee satisfaction. The author has taken notice that causal relations distinguished in the Excellence Model EFQM between its categories (modules) are of more complex character. The power of connection is determined by existing latent variables. They have been identified in relation to the causal model of employee satisfaction. Their influence range has been also defined. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 467-476